A rationale for modeling hydrogen effects on plastic deformation across scales in FCC metals - Castelluccio, Gustavo M.; Geller, Clint B.; McDowell, David L. (Elsevier, 2018)
Although there have been many investigations on the effects of hydrogen on the plastic deformation of metals, an intense debate continues about the physical mechanisms responsible. Most puzzling is the fact that hydrogen appears to be able to both harden and soften FCC metals, depending on the loading conditions. In addition, experiments have shown that hydrogen affects slip system activity differentially, resulting in shear localization of plastic deformation. The work reported in this paper employs a physics-based crystal plasticity model to reproduce the macroscopic response of hydrogen-charged FCC metals through the hydrogen effects on dislocation interactions proposed herein. Different micro-scale mechanisms by which hydrogen may affect plastic deformation are considered, and their resulting macroscopic stress-strain responses under monotonic and cyclic loading are compared. The results support the conclusion that hydrogen screening of dislocations alone cannot explain all the observed macroscopic responses. Instead, it is argued that hydrogen can promote hardening or softening through an increase in glide activation energy and a reduction in dislocation line tension.